1998
DOI: 10.1002/(sici)1097-4547(19980715)53:2<251::aid-jnr14>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Sustained neonatal hyperthyroidism in the rat affects myelination in the central nervous system

Abstract: We have carried out a study of the effects of sustained neonatal hyperthyroidism on myelin and on the oligodendroglial cells, in an effort to obtain further insight into the molecular mechanisms underlying the action of thyroid hormones on the central nervous system (CNS). Expression of the mRNAs of myelin basic protein (MBP) myelin proteolipid protein (PLP), 2',3'-cyclic nucleotide 3'-phosphodiesterase (CNPase), transferrin, and c-Jun was investigated in 10- and 17-day-old normal and hyperthyroid rats, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 19 publications
3
46
0
Order By: Relevance
“…Moreover, A1254 exerted selective effects on the expression of TH-responsive genes because NSP-C, which is not influenced by TH in the fetus (Dowling et al , 2001, was not affected by A1254. Furthermore, previous work in our laboratory has demonstrated that A1254 increases the expression of myelin basic protein, a known TH-responsive gene (Farsetti et al 1991;Marta et al 1998;Rodriguez-Pena et al 1993), in the cerebellum and RC3/neurogranin in the forebrain of postnatal rats, despite the finding that these pups exhibited a Article | Gauger et al Assays were performed to determine whether PCBs present in A1254 were able to alter the affinity TRs for T 3 . Isolated nuclei were incubated with 1.0 nM 125 I-T 3 , and increasing concentrations (1 × 10 -12 M to 1 × 10 -6 M) of T 3 alone or with increasing concentrations (1 × 10 -12 M to 1 × 10 -6 M) of T 3 in the presence of 20 µM of the PCB competitor.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, A1254 exerted selective effects on the expression of TH-responsive genes because NSP-C, which is not influenced by TH in the fetus (Dowling et al , 2001, was not affected by A1254. Furthermore, previous work in our laboratory has demonstrated that A1254 increases the expression of myelin basic protein, a known TH-responsive gene (Farsetti et al 1991;Marta et al 1998;Rodriguez-Pena et al 1993), in the cerebellum and RC3/neurogranin in the forebrain of postnatal rats, despite the finding that these pups exhibited a Article | Gauger et al Assays were performed to determine whether PCBs present in A1254 were able to alter the affinity TRs for T 3 . Isolated nuclei were incubated with 1.0 nM 125 I-T 3 , and increasing concentrations (1 × 10 -12 M to 1 × 10 -6 M) of T 3 alone or with increasing concentrations (1 × 10 -12 M to 1 × 10 -6 M) of T 3 in the presence of 20 µM of the PCB competitor.…”
Section: Discussionmentioning
confidence: 99%
“…During the first 3 postnatal weeks in the rat and mouse, two genes have been most extensively studied for their responsiveness to thyroid hormone: RC3/neurogranin in the forebrain and myelin basic protein (MBP) in the cerebellum (138)(139)(140)(141). The expression of both of these genes is up-regulated by thyroid hormone (139,142).…”
Section: In Infantsmentioning
confidence: 99%
“…Myelination, for example, is delayed in hypothyroid animals (Dussault and Ruel, 1987;Rodriguez-Pena et al, 1993) and accelerated in hyperthyroid animals (Marta et al, 1998;Walters and Morell, 1981). Moreover, perinatal hypothyroidism decreases the number of oligodendrocytes in the optic nerve of the rat (Ibarrola et al, 1996) and mouse (Ahlgren et al, 1997).…”
Section: Introductionmentioning
confidence: 99%